Kecerdasan Spiritual Kristen dalam Mengelola Stres dan Peran Ganda Orang Tua Tunggal - Noh Ibrahim Boiliu; Meike Lely Lewankoru; Ribka (Sekolah Tinggi Teologi SAPPI Ciranjang, 2025)
Single parents face complex challenges in the form of dual roles as breadwinners and primary caregivers, which often trigger high levels of stress due to economic pressures, caregiving demands, and limited social support. This study aims to analyze the role of Christian spiritual intelligence in stress management among single parents. The method used is a literature review of scientific articles discussing the relationship between spirituality, coping, and psychological well-being. The findings show that Christian spiritual intelligence functions as an emotion-based coping mechanism that helps regulate emotions, provides transcendent meaning, and strengthens psychological resilience. Faith practices support have been shown to reduce social isolation and increase a sense of belonging, making single parents more resilient in facing life's pressures. This article contributes by offering a conceptual framework that integrates Christian spirituality, coping strategies, and social support as the foundation for stress management.